Analisis Yuridis Normatif terhadap Efektifitas Hukum dalam Penindakan Tindak Pidana Korupsi di Indonesia: Tinjauan terhadap Peran Hukum Pidana - Alfarizi, Vika Amalia (UM Purwokerto Press, 2024)
Corruption is a serious problem that damages the social, economic and political order in various countries, especially Indonesia. Corruption has a broad and detrimental impact on society and the state, such as obstruction of development, reduced public trust in institutions, and social and economic disparities. The purpose of this research is to find out how the effectiveness of criminal law in prosecuting corruption in Indonesia based on normative juridical analysis and how the application of criminal law in prosecuting corruption in Indonesia. The type of method used by the author in this research is Normative Juridical research, which is a library legal research conducted by examining library materials or periodic secondary data. Thus the object analyzed with a qualitative approach is a research method that refers to the legal norms contained in the legislation. The conclusion of this research is that as a state of law, Indonesia must carry out a law enforcement process for corruption to ensure the rule of law, justice and peace in society. However, it is clear that law enforcement of corruption in Indonesia is still weak. This is due to the fact that there are still many lawmakers or law enforcers who commit corruption. The existence of lawmakers or law enforcers who commit corruption can reduce public trust in them. And the advice that can be given is that the government needs to revise the laws related to the eradication of corruption to eliminate legal loopholes that can be utilized by perpetrators of corruption. The application of strict sanctions in accordance with the level of crime committed must be carried out to show the government's commitment to eradicating corruption. It is also hoped that the government will harmonize the corruption law with other related regulations to avoid overlap and ensure harmony in law enforcement.